PENGARUH KREATIFITAS PEGAWAI, IKLIM ORGANISASI, BUDAYA ORGANISASI, KEPEMIMPINAN TRANSFORMASIONAL, DAN PEMBERDAYAAN TERHADAP KINERJA PEGAWAI - Imbaruddin, Amirul; Wijayanto, Andi; Ngatno, Ngatno (Jurnal Administrasi Negara, 2024)
This study was conducted to explore the affect of employee creativity, organizational climate, organizational culture, transformational leadership, and employee engagement on employee performance at Accounting Firms through employee satisfaction and work engagement as a mediating variabel. This study uses quantitative methode and structural equation modeling (SEM). This research then involved 200 respondents selected from accounting firm employees in Makassar. The results of the study show that employee creativity and organizational climate significantly influence employee satisfaction and work engagement, which has a positive impact on employee performance. Furthermore, transformational leadership and organizational culture have been proven to improve employee performance. However, employee empowerment has been proven to increase employee motivation and performance. This conclusion match with the theory which states that employee satisfaction and work commitment play an important role as mediating variabels in the relationship between the work environment and employee performance. Therefore, this study contributes to the performance management literature by highlighting the importance of these variabels in improving performance in the service sector. Practical implications show that companies in the service sector develop positive organizational cultures, transformational leadership styles, and employee empowerment strategies to improve performance.